Periphytic Algae and Cyanobacteria from the Rio Doce Basin Respond Differently to Metals and Salinity, Showing Different Potential for Bioremediation - Marcelo Pedrosa Gomes (MDPI AG, 2021)
We have studied the isolated and combined effects of metals (Fe and Mn) and NaCl the on growth, physiology, and metal-uptake capacity of two photosynthetic periphytic species—Synechococcus elongatus (Cyanobacteria) and Chlorococcum infusionum (Chlorophyta)—isolated from an impacted area of the Rio Doce River (Brazil) after the Fundão dam collapse. The effective concentrations found to reduce 10 and 50% growth were 15.2 and 31.6 mg Fe L−1, and 2.5 and 7.9 mg Mn L−1 for S. elongatus and 53.9 and 61.6 mg Fe L−1, and 53.2 and 60.9 mg Mn L−1 for C. infusionum. Although the metal toxicity was related to oxidative stress, both species showed activation of antioxidant systems under phytotoxic concentrations of Fe and Mn. By binding large concentrations of metals on its cell surface and thus avoiding their entrance into the cells, C. infusionum presents greater resistance to Fe and Mn than S. elongatus. Under environmental realistic concentrations of Fe and Mn in river water from the Rio Doce Basin, S. elongatus and C. infusionum showed a metal removal efficiency of 42 and 65% and 53 and 79%, respectively after 96 h. These species were insensitive to increased NaCl concentrations which, in addition, did not disrupt the metal removal capacity of the species. Due to their salt and metal tolerance, S. elongatus and C. infusionum can be used for the remediation of waters contaminated with Fe and Mn.